Sosialisasi Peraturan Cabang Olahraga Voli Pada Guru Penjas Se-Kecamatan Cimanggu Kabupaten Cilacap - Dian Imam Saefulah; Kusmiyati; Ghozali (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2021)
Community service is non-formal education for physical education teachers in schools, through educational activities, and educational outreach that can support community development. Education for the community is one of the implementations of the tri-dharma of higher education. Community service through the socialization of volleyball sport rules to physical education teachers throughout Cimanggu District, Regency. Cilacap. is an effort to: (1) find out and provide an understanding of the level of sports human resource management knowledge of physical education teachers in schools throughout Cimanggu District; (2) know and describe the potential of sports human resources in schools throughout Cimanggu District. This Community Service is carried out to provide education to Physical Education teachers in each school about the Volleyball Sports Rules for Physical Education Teachers and identify talents in schools from an early age to create a generation of outstanding people. As a result of this community service, there has been an increase in knowledge about skills in preparing training programs and understanding in identifying children's talents in looking for athletes in schools, especially in the field of Volleyball.